Process and Characterization of Natural Rubber Modification (Sir-20) With Grafting Maleat Anhydride - Murdoni Sipayung; Eddyanto Eddyanto (Indonesian Journal of Chemical Science and Technology (IJCST), 2022)
Modification of natural rubber by Grafting method using monomer maleate anhydride is a technique of  modification of natural rubber polymers that aims to change the physical and chemical sifak of natural rubber  polymers. The grafting process is carried out by comparing the amount of MA that is graphed based on the type of peroxide, the variation of peroxide concentration and the variation of MA concentration. FTIR test results showed the appearance of peak absorption at the wave number of 1710-cm cluster C=O carbonyl from MA that is graphed in natural rubber.. Based on the comparison of ir analysis of peroxide concentration used i.e. (0.01, 0.05 and 0.1) molar ratio obtained the largest carbonyl index at DCP concentration of 0.05 mr similarly, the  comparison of IR analysis results of MA concentration variations (3, 6, 9, 12) phr shows the largest carbonyl  index that appears in the C=O absorption area is in the KA-g-MA sample with a MA variation of 12 phr with  Carbonyl index = 45.81. The degree of MA grafting on natural rubber structures increases with increased MA concentration.